Critical roles of m6A methylation in cardiovascular diseases - Zhang, Xinmin; Cai, He; Xu, He; Dong, Su; Ma, Haichun (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVDs) have been established as a major cause of mortality globally. However, the exact pathogenesis remains obscure. N6-methyladenosine (m6A) methylation is the most common epigenetic modification on mRNAs regulated by methyltransferase complexes (writers), demethylase transferases (erasers) and binding proteins (readers). It is now understood that m6A is a major player in physiological and pathological cardiac processes. m6A methylation are potentially involved in many mechanisms, for instance, regulation of calcium homeostasis, endothelial function, different forms of cell death, autophagy, endoplasmic reticulum stress, macrophage response and inflammation. In this review, we will summarize the molecular functions of m6A enzymes. We mainly focus on m6A-associated mechanisms and functions in CVDs, especially in heart failure and ischemia heart disease. We will also discuss the potential application and clinical transformation of m6A modification.